The Nuer a description of the modes of livelihood and political institutions of a Nilotic people - Evans-Pritchard, E. E. (Edward Evan) 1902-1973 (Oxford Clarendon Press, 1940)
"Considerable part of the facts related have been previously recorded, chiefly in Sudan notes and records, and Africa."-Preface.
Includes index.
Keywords: Nuer (African people).